Penerapan Life Cycle Assessment Material Arsitektur Pada Pembangunan Gedung Rumah Sakit Di Kota Malang - Muchammad Rizal Fahmi; Apif Miptahul Hajji; Imam Alfianto (Universitas Andalas, 2026)
The construction sector is a major contributor to greenhouse gas emissions, accounting for 20% of the total emissions that impact global warming. Based on a report from the IPCC the construction sector is responsible for 40% of global energy consumption. The purpose of this research is to identify and evaluate the life cycle of materials in architectural work. The scope of Life Cycle Assessment in this research is cradle to gate where the research is carried out starting from material collection, transportation, to implementation. This research will estimate the environmental impact of the use of materials for architectural work in the construction of hospital in Malang City. Life Cycle Assessment analysis using SimaPro 9.5 software. The method used is observation survey method and data collection. Based on the results of the study, it was obtained that the material that has a major contribution to environmental impacts, especially global warming, is lightweight brick material in wall work. Lightweight bricks have the largest contribution to wall work because the material in lightweight bricks contains cement composition, which has the largest carbon emissions in construction.